IMPLEMENTASI PENDIDIKAN KARAKTER YANG TERINTEGRASI DALAM PEMBELAJARAN EKONOMI DI SMA NEGERI 2 MAGELANG - Annisaa Rahmawati; Dewi Kusuma Wardani; Leny Noviani (Department of Economics Education, Universitas Sebelas Maret, 2018)
The research aims to describe of planning, implementation, and evaluation problems that facting by the economic teachers on the implementation of integrated character education in economics learning at the SMA Negeri 2 Magelang. This study used a qualitative descriptive method with a case study approach.Sampling technique used were purposive sampling and snowball sampling. Data collection techniques used were observation, interviews, and analysis of data validity test document with data analysis techniques interactive analysis Miles & Huberman. Based on the research obtained conclusions that, planning by drafting character from of lesson, implementation is done by habituation, exemplary, and intervention of character values are internalized to the economics learning, cultivation of character values in the economics learning through the affective aspects evaluated in observation sheet with indicators of honest attitude, discipline, responsibility, caring, and hard work, constraints faced by economic teachers that teachers still find it difficult to incorporate the values of the characters according to instructional materials, conditions and interests of learners that are still lacking, teachers are still difficulties in using learning model matching the economy's material, and teachers are still difficulties in assessing the student's character.